Makna Filosofis ’’Odak ’’ Dalam Ritual ’’Barodak Rapancar’’ - Indra Susanto (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
The barodak rapancar traditional ceremony is one of the traditional rituals Samawa tribal wedding. Barodak rapancar is a tradition of the bride and groom scrub with traditional ingredients called odak. In the ceremony This rapancar baroque has hidden messages as seenin symbols or tools used in its implementation. But alongthe flow of globalization this tradition is gradually fading, this is because some people, especially the younger generation, do not knowthe meanings contained in the barodak tradition of rapancar. In the Sumbawa district itself, there is a customary tradition of marriage for the Samawa tribe, especially in the Batudulang Village community, which is located in Batulanteh District, the Batudulang Village community still preserves the cultures passed down by their ancestors, one of which is the marriage. The aim of the research to be achieved is to know the philosophical meaning contained in odak in the Barodak Rapancar tradition in the marriages of the Samawa people. Based on the results of the analysis and information that has been found by the reviewers, it can be concluded that several things related to this research are as follows: The Barodak Rapancar tradition is one of the Sumbawa traditional marriage processes. The barodak tradition is scrubbing using traditional materials and the Rapancar process of coloring the hands using traditional ingredients. The barodak tradition consists of three stages, namely the bridal shower (maning bride), bridal odak and odak odak (odak disposal). The Barodak Rapancar tradition is one of the Sumbawa traditional marriage processes. The barodak tradition is scrubbing using traditional materials and the Rapancar process of coloring the hands using traditional ingredients. The barodak tradition has three stages, namely the bridal shower (maning bride), the bridal shower and the odak ball (throwing odak). The philosophical meaning of Odak in the Barodak Rapancar ritual is as follows where Odak symbolizes the sincerity of one heart and determination, while Barodak Rapancar itself has the meaning of Barodak asa form of self-cleaning in the framework of carrying out a sacred promise or agreement, badaet cleans up the residue of evil on the bride and groom before the wedding day, while rapancar is intended to provide a bright pattern of light so that it gives the color of joy and love and is a sign that the two couples are married.